História da formação docente por meio da faculdade adventista de educação - FAED contribuições para a formação de professores no Brasil - Sales, Giza Guimarães Pereira (Editora Oficina Universitária, 2022)
With this precious historiographical work developed through the recovery, selection and organization of documentary sources, the author portrayed the daily life and the organizational aspects of the Adventist College of Education, of the Adventist Institute of Education, currently called Centro Universitário Adventista de São Paulo (UNASP) . It focused on the analysis of laws, decrees, ordinances and a set of institutional documents such as a pedagogical project, regulations, minutes, record books and the curriculum of the disciplines taught in the Pedagogy course, the first higher education teacher training course at that institution, with the objective of perceiving whether the didactic-pedagogical training model present in its confessional matrix was in line with the official documents and with the academic requirements necessary for teacher training, advocated at that historical moment.